Assessing the impacts of Light Rail Transit on urban land in Manila - Pacheco-Raguz, Javier F. (Journal of Transport and Land Use, 2010)
This paper presents an assessment of impacts of Light Rail Transit Line 1 (LRT1) in terms of accessibility and distance as they relate to variables such as land values, land uses, and population densities in Manila, Philippines. Using correlations and regressions, these variables are analyzed against an accessibility index and network distances obtained from a model built within a Geographic Information System (GIS). Land values, land uses, and population densities are influenced in a limited, though consistent, way by the accessibility provided by LRT1 and the distance to it. The analysis of impacts after the construction of LRT1 found that accessibility and distance were only consistent influences for residential land values, with marginal results for the rest of the variables. These results, when contrasted with the urban configuration of Manila and the studies reviewed, show that the limited impacts may be a consequence of good accessibility before LRT1 and the lack of complementary planning and policies for taking advantage of its influence.